Audit of cesarean delivery in Burkina Faso. Issue 3 (15th February 2014) - Kouanda, Seni; Coulibaly, Abou; Ouedraogo, Ali; Millogo, Tieba; Meda, Bertrand I.; Dumont, Alexandre
Abstract: Objective: To assess the level and determinants of unnecessary cesarean delivery. Methods: In a retrospective study, the medical charts were reviewed for 300 low‐risk women who underwent intrapartum cesarean delivery at 10 referral hospitals in Burkina Faso between May 2009 and April 2010. In this context, cesarean deliveries were delegated to clinical officers who have less training than doctors. Results: Among the 300 study patients, 223 women (74.3%) were referred from primary healthcare facilities. The reason for referral was not medically justified for 35 women. Cesarean was performed by a gynecologist–obstetrician (46.0%), a trained doctor (35.0%), or a clinical officer (19.0%). Acute fetal distress and fetopelvic disproportion were the main indications recorded for intrapartum cesarean delivery. These diagnoses were not confirmed by an obstetrician–gynecologist in 12.0% of cases. Clinical officers were associated with a higher risk of unnecessary cesarean delivery compared with gynecologist–obstetricians by multivariate analysis (odds ratio, 4.46; 95% confidence interval, 1.44–13.77; P = 0.009). Conclusion: Verification of cesarean indications by highly qualified personnel (i.e. second opinion), in‐service training, and supervision of health workers in primary healthcare facilities might improve the performance of the referral system and help to reduce unnecessary cesarean deliveries in Burkina Faso.